THE INFLUENCE OF CLASSIC MUSIC T PENGARUH PEMBERIAN TERAPI MUSIK KLASIK TERHADAP PENURUNAN TINGKAT KECEMASAN PADA IBU BERSALIN DI KLINIK ROMAULI MARELAN TAHUN 2023 - Endryani Syafitri; Muthia Sari Mardha; Friska Yuni Simatupang (Jurnal Ilmu Kebidanan, 2023)
Introduction: Labor and birth are physiological things that almost every woman will experience. However, even though this is a physiological thing, it will make the mother feel anxious because during the labor process she will experience excruciating pain, pain during labor can reduce the uterus' ability to experience contractions, thereby lengthening the time during the labor process. The discomfort experienced by someone who is about to give birth will increase and can cause anxiety. Objective to determine the characteristics of respondents (based on age, education, occupation, parity), to determine the level of anxiety, to determine the effect of providing classical music therapy on reducing maternal anxiety levels before and after being given classical music therapy. birth at the Romauli Marelan Clinic in 2023. The research design used in this study was a quasi-experimental design with a one group type pretest and posttest design. Results: From research that obtained the level of maternal anxiety before treatment, the normality test results were 0.178 > 0.05, which means the data was not normally distributed, then the Wilcoxon test was carried out and obtained a significant value of P=0.000 where p<0.05, "there is an effect of therapy classical music on reducing anxiety levels in mothers giving birth. there is an influence of classical music in reducing anxiety levels in mothers giving birth. Music therapy can help mothers relax and provide early stimulation to the fetus, so it is recommended as an effective intervention for mothers in labor.